TRIP PLANNER OVER PROBABILISTIC TIME-DEPENDENT ROAD NETWORKS - T, Reshmi.; Krishna, N.Santhana (IJRDO -Journal of Computer Science Engineering, 2016)
In recent times, the management of transportation systems has turn into increasingly important in many real applications such as location-based services, traffic control, and so on. These applications usually absorb queries over spatial road networks with energetically changing and complex traffic conditions. In this paper, we proposed such a network by a probabilistic time-dependent graph referred as PT-Graph, whose edges are connected with uncertain delay functions. In this paper we propose a functional query in the PTGraph, known as trip planner query (TPQ), which retrieves trip plans that traverse a set of query points in PT-Graph. To tackle the efficiency issue, we proposed the pruning methods which include time interval pruning and probabilistic pruning to effectively rule out false alarms of trip plans.